Coping beyond adversity: living with a spinal cord injury - Allsop, Gary (Henry Stewart Talks, 2011)
Living with a spinal injury, A detailed insight into what it is like to live with a spinal cord injury, Explaining every danger and risk associated with living with such a disability
Updated at 2016/02/29